Fecal metabolomics analysis for deciphering the lipid-lowering effect of Qizhi capsule on high-fat feed induced hyperlipidemia. (23rd May 2023) - Ren, Junling; Fang, Heng; Yang, Le; Sun, Hui; Song, Hongwei; Yan, Guangli; Han, Ying; Wang, Xijun
Abstract: Ethnopharmacological relevance: Qizhi capsule (QZC), a Chinese patent drug, has been utilized to treat hyperlipidemia. Aim of study: The present study aims to investigate the lipid-lowering effect of QZC, as well as the mechanism of action for treating hyperlipidemia. Materials and methods: High-fat diet (HFD) induced hyperlipidemia rats were administrated with different doses of QZC for 28 days, and atorvastatin calcium tablets was used as the positive control. Serum total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C), and high-density lipoprotein cholesterol (HDL-C) levels were used to evaluate the effectiveness of QZC treatment. The metabolic profiles of feces were analyzed by UPLC-MS-based metabolomics approach coupled with multivariate data analysis. Results: The levels of serum TC, TG, LDL-C, and HDL-C were significantly reversed in QZC treatment groups, showing a similar or even better treatment effect compared with the atorvastatin calcium group. Thirty-two potential fecal biomarkers related to hyperlipidemia were identified. QZC could partially recover the disturbed metabolic pathways of alpha-linolenic acid metabolism, sphingolipid metabolism, glycerophospholipid metabolism, and glycosylphosphatidylinositol (GPI)-anchor biosynthesis. Meanwhile, the signal pathways of regulation of lipid metabolism by peroxisome proliferator-activated receptor α (PPARα), PPARα activates gene expression, and transcriptional regulation of white adipocyte differentiation can be also regulated by QZC. Conclusion: The lipid-lowering effect of QZC was confirmed by both serum biochemistry and metabolomics analysis. The beneficial effects of QZC were mainly attributed to the correction of metabolic disorders and the maintenance of the dynamic balance of metabolites. Graphical abstract: Image 1 Highlights: Qizhi capsule exhibits lipid-lowering effect. Fecal metabolism deciphered the potential mechanism of action of Qizhi capsule. PPARα and white adipocyte differentiation might be the targets of Qizhi capsule for treating hyperlipidemia.